Simulation Analysis of Harmonic Mitigation in Solar Photovoltaic Based Microgrid System - Kaur, Jaspreet; Khosla, Anita (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The increasing concern on contamination and a perilous atmospheric deviation has provoked the Photovoltaic (PV) framework as one of the conceivable, inexhaustible and clean energy in power framework generation. Power quality problems like Total Harmonic Distortion (THD) have become an inexorably genuine problem as more Photovoltaic setups are coordinated into the grid framework. This urges a broad analysis to distinguish the challenges in power system organization. The proposed microgrid model consists of MPPT-Maximum Power Point Tracking system, a converter, and a multi-stage inverter. In this study, power active and passive filters are utilized; further cases are analyzed for power quality issues to reduce the harmonics using MATLAB simulation.